2013
DOI: 10.1371/journal.pone.0061444
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteome Analysis of Chikungunya Virus Infection on Host Cells

Abstract: BackgroundChikungunya virus (CHIKV) is an emerging mosquito-borne alphavirus that has caused multiple unprecedented and re-emerging outbreaks in both tropical and temperate countries. Despite ongoing research efforts, the underlying factors involved in facilitating CHIKV replication during early infection remains ill-characterized. The present study serves to identify host proteins modulated in response to early CHIKV infection using a proteomics approach.Methodology and Principal FindingsThe whole cell proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 41 publications
11
74
3
Order By: Relevance
“…Abere and colleagues looked at the changes in CHIKV infected CHME‐5 microglial cells initially by 2D electrophoresis and observed some 59 altered spots, a number consistent with the 53 differentially regulated protein spots seen by Thio and colleagues who investigated the changes in CHIKV infected WRL‐68 cells. Although Thio and colleagues moved directly to the analysis of the protein spots through matrix‐assisted laser desorption/ionization‐tandem time‐of‐flight (MALDI‐TOF/TOF), Abere and colleagues undertook subsequent analysis through GeLC‐MS/MS and identified some 90 significant differentially regulated proteins. Thio and colleagues successfully identified 50 of the spots, which mapped to 45 distinct proteins as shown in Table 1 of their study .…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 67%
See 2 more Smart Citations
“…Abere and colleagues looked at the changes in CHIKV infected CHME‐5 microglial cells initially by 2D electrophoresis and observed some 59 altered spots, a number consistent with the 53 differentially regulated protein spots seen by Thio and colleagues who investigated the changes in CHIKV infected WRL‐68 cells. Although Thio and colleagues moved directly to the analysis of the protein spots through matrix‐assisted laser desorption/ionization‐tandem time‐of‐flight (MALDI‐TOF/TOF), Abere and colleagues undertook subsequent analysis through GeLC‐MS/MS and identified some 90 significant differentially regulated proteins. Thio and colleagues successfully identified 50 of the spots, which mapped to 45 distinct proteins as shown in Table 1 of their study .…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 67%
“… Studies are identified by the first name of the author and where required, the year (Thio ; Abere ; Dhanwani (2011) ; Dhanwani (2014) ; ; Fraisier ; Wikan ; Puttamallesh ) and the protein ID or accession number listed in the study is given. Where required the proteome (liver or brain) or technique (DIGE or iTRAQ) is also indicated.…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search parameters used were as previously described [5]. Proteins were represented as nodes and their functional links were defined by solid lines.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in high throughput technologies, such as transcriptomics and proteomics, for pathogen-host interaction studies [25,52,96,109,117,136], as well as the publication of several vector species genomes including the mosquitoes Culex quinquefasciatus [2], Anopheles gambiae [49] and Aedes aegypti [89] and the tick Ixodes scapularis [46], have led to the discovery of immunity pathway orthologues in these species [65,105]. While there is no midge genome available to date, recent combined efforts of The Pirbright Institute and the European Bioinformatics Institute (part of the European Molecular Biology Laboratory; EBI-EMBL) have led to the first full de novo sequencing project for Culicoides sonorensis.…”
Section: Introductionmentioning
confidence: 99%